2018
DOI: 10.1093/jnci/djy106
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer Risk Genes Identified by Multigene Hereditary Cancer Panel Testing

Abstract: BackgroundGermline genetic testing with hereditary cancer gene panels can identify women at increased risk of breast cancer. However, those at increased risk of triple-negative (estrogen receptor–negative, progesterone receptor–negative, human epidermal growth factor receptor–negative) breast cancer (TNBC) cannot be identified because predisposition genes for TNBC, other than BRCA1, have not been established. The aim of this study was to define the cancer panel genes associated with increased risk of TNBC.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
226
5
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 240 publications
(278 citation statements)
references
References 25 publications
26
226
5
21
Order By: Relevance
“…More recently, a study of 8753 TNBC subjects found a mutation rate of 14.4% through a 17-gene panel test. 20 In our current analysis, the overall prevalence of germline mutations was also higher in the TN (24%) and ER-and PR-positive/HER2-negative subtypes (13%), but the prevalence was lower in IBC subjects with HER2-positive disease (5.6%).…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…More recently, a study of 8753 TNBC subjects found a mutation rate of 14.4% through a 17-gene panel test. 20 In our current analysis, the overall prevalence of germline mutations was also higher in the TN (24%) and ER-and PR-positive/HER2-negative subtypes (13%), but the prevalence was lower in IBC subjects with HER2-positive disease (5.6%).…”
Section: Discussionsupporting
confidence: 38%
“…In Tung et al’s study, the prevalence of germline mutations varied according to the breast cancer subtype: 17.2% in TN disease, 8.6% in ER‐ and PR‐positive/HER2‐negative disease, and 10.8% to 11.1% in HER2‐positive disease. More recently, a study of 8753 TNBC subjects found a mutation rate of 14.4% through a 17‐gene panel test . In our current analysis, the overall prevalence of germline mutations was also higher in the TN (24%) and ER‐ and PR‐positive/HER2‐negative subtypes (13%), but the prevalence was lower in IBC subjects with HER2‐positive disease (5.6%).…”
Section: Discussionmentioning
confidence: 69%
“…history of the disease. 8 RAD51C and RAD51D have recently been suggested as risk genes for triple-negative BC, 19 while their contribution to OC with a fiveto sixfold increased risk has been acknowledged longer. [16][17][18] We have previously identified FANCM as a BC predisposing gene in the Finnish population with approximately twofold increased risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] RAD51C and RAD51D have been identified primarily as OC susceptibility genes, but have recently been linked also to triple-negative BC. [16][17][18][19] In addition, genome-wide association studies have reported numerous common risk-modifying alleles. 20 In the Finnish population, the history of geographic isolation and genetic bottlenecks has led to reduced variation and enrichment of deleterious alleles.…”
Section: Introductionmentioning
confidence: 99%
“…PVs in CHEK2 , ATM and PALB2 were also identified in 0.5% of patients, but a cost–benefit analysis would be needed before including them as opportunistic testing beyond the patient's phenotype. Regarding BARD1 , the role of this gene in BC susceptibility is currently being investigated with a potential significant association with triple negative BC. It is not clear if a relative risk of 3–4 for triple negative BC will be clinically relevant due to the lower prevalence of triple negative BC and, therefore, a lower absolute risk.…”
Section: Discussionmentioning
confidence: 99%